SOSIALISASI DAN PELATIHAN PENGOLAHAN JELLY NATA SIAP SAJI DAN MINUMAN NATA READY TO DRINK PADA UKM NATA DE COCO DI KOTA PRABUMULIH - Eka Lidiasari; Merynda Indriyani Syafutri; Parwiyanti Parwiyanti; Friska Syaiful; Tri Wardani Widowati; Filli Pratama; Umi Rosidah (Bajang Institute, 2023)
UKM KsP and UKM Triliyat are businesses that produce nata de coco in Prabumulih City, South Sumatra Province. During this time, both produce and market packaged nata de coco. Nata de coco has the potential to be developed into products such as ready to eat jelly and ready to drink beverages. This community service activity aimed to provide socialization and counseling to UKM KsP and UKM Trilliyat about processing and packaging technology for ready to eat nata jelly product and ready to drink nata beverages product. The activity stage consisted of three, namely the socialization and counseling stage, the independent practice stage, and testing the sensory properties stage. The methods used were material explanation and discussion, practice, and sensory testing. The results of the activity showed that nata de coco can be developed into ready to eat nata jelly product and ready to drink nata beverages product. In addition, UKM KsP and UKM Triliyat had been able to process ready to eat jelly nata product and ready to drink nata beverages product with attractive packaging. Ready to eat nata jelly product and ready to drink nata beverages product had sensory properties (appearance, aroma, taste, and texture) that were accepted and liked by panelists.